Development of an approach for operative control over railway transport technological safety based on the identification of risks in the indicators of its operation - Samsonkin, Valerii; Goretskyi, Oleksii; Matsiuk, Viacheslav; Myronenko, Viktor; Boynik, Anatoliy; Merkulov, Viktor (Eastern-European Journal of Enterprise Technologies, 2019)
The paper addresses the mechanism of ensuring and management of traffic safety in railway traffic. It uses the actual statistics on the cases of violations of traffic safety along the railways of Ukraine over recent years. We have selected three departments for empirical research and justification of the need for a systematic approach. The departments account for 60 % of traffic accidents a year. The departments include a locomotive department, tracks department and carriages department. A systematic approach to technological safety management has been proposed. It uses safety violation statistics as input information. It systematizes each safety violation accident according to eight parameters that characterize location, time, type of case, its cause, guilty party, circumstances, motivation, and targeted damage. It creates the appropriate database with systematization parameters. The analysis of dynamics of traffic accidents in the one-, two-, and three-dimensional space of systematization parameters detected hidden patterns, which pose a threat of deterioration of safety and occurrence of emergency. We interpreted this as a bottleneck, which requires increased attention and development of measures to prevent escalation into an emergency. We defined a risk as the most significant prerequisite for traffic accidents. Prerequisites are in the plane of ensuring of a transportation process, and they are systemic in nature. The developed algorithm for operative management of technological safety and a procedure for support of making operative management decisions reduce the impact of risks. The algorithm is formalized and ready for automation. Automation involves application of 4.0 digital technologies. Application of the proposed approach will help to reduce an impact of the human factor, to increase efficiency and objectivity of management decisions for ensuring of safety, and to make safety financing targeted and effective. It is possible to apply the proposed approach to other modes of transportation